Study of Physical and Chemical Parameters to Evaluate the Quality of Drinking Water for Some Groundwater Wells in the City of Al-Bayda, Libya (Sebha University Conference Proceedings, 2024)
The purpose of this work was to investigate the physicochemical characteristics to find the quality of groundwater and whether it is suitable for drinking purposes or not. Ten sites were selected in the Al-Bayda city and three replicates were taken from each well site.  The current study's results show that there are differences between stations. In contrast, the pH values varied between (7.63 - 7.92), TDS values ranged between (285 - 493.33 mg/L), EC values were ranged (593.33 - 864.67 μS/cm), The values of alkalinity (measured as HCO3-) varied from (262.6 - 341.6  mg/L), The range of total hardness values was from (253.54 - 308.25 mg/L), The range of Ca++ levels was (88.18 - 122.38 mg/L), Mg++ (52.8 - 73.92 mg/L), Cl- (44.90 - 89.81 mg/L), Na+ (26.41- 53.99 mg/L), K+ (0.48 - 5.81 mg/L), and NO3- (0.27 - 4.46mg/L). The findings showed that the values of pH, EC, TH, TDS, Cl-, Ca++, Na+, K+ and NO3- were found to be within the permissible limit values. On the other hand, the values of Alkalinity, and Mg++ exceeded the acceptable limit. All parameters vary depending on the nature of the terrain, geological structure, and soil. Based on the aforementioned findings, the local government should establish more water filtration plants and conduct routine water quality monitoring to provide safe drinking water.